2019
DOI: 10.2337/dc19-0567
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Disasters on Seniors With Diabetes: Evidence From Hurricanes Katrina and Rita

Abstract: To estimate the long-run mortality effects of Hurricanes Katrina and Rita on seniors with diabetes. RESEARCH DESIGN AND METHODS We performed a retrospective cohort analysis of Medicare enrollment and claims data covering four states and ∼10 years. Affected individuals were identified by whether they lived in a county that suffered a high impact and were stratified by whether they moved to a different county following the storms. Propensity scores matched affected and comparison subjects based on demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…2 Elevations in postdisaster geriatric emergency department visits 15 and cardiac events 16 were seen after Hurricane Sandy, and also in a combined study looking at Hurricanes Rita and Katrina. 3,17 This study also found significant increases in all-cause hospital admissions when examining eight separate, large-scale hurricanes. Prior research has described surges in hospitalization after hurricanes, however most of these reports have been limited to one disaster 18 or the immediate period after a disaster.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…2 Elevations in postdisaster geriatric emergency department visits 15 and cardiac events 16 were seen after Hurricane Sandy, and also in a combined study looking at Hurricanes Rita and Katrina. 3,17 This study also found significant increases in all-cause hospital admissions when examining eight separate, large-scale hurricanes. Prior research has described surges in hospitalization after hurricanes, however most of these reports have been limited to one disaster 18 or the immediate period after a disaster.…”
Section: Discussionsupporting
confidence: 53%
“…These long-term effects include changes in health behaviors, excess hospitalizations, and in some cases, mortality. 1,2 Other studies have examined the impact of diabetes-related hospital admissions after Hurricanes Katrina (2005) and Rita (2005), 3 hypertension among US veterans, 4 and of course, Hurricane Maria (2017) related mortality. 5 Prior studies limited to examining a single disaster suggest that exposure to hurricanes may affect the health of older adults.…”
Section: Introductionmentioning
confidence: 99%
“… [7] Even though of different magnitude, suspension of healthcare services is well studied in post-disaster recovery phases: Katrina and Rita hurricanes raised crude mortality rate of 40% in the month following the disaster, and this increment remained after a year (12%) and even after ten years (5.6%). [8] …”
Section: Introductionmentioning
confidence: 99%
“…379 Seniors with diabetes who lived in a county highly impacted by Hurricanes Katrina and Rita (N = 170,138), compared to those who did not (N = 170,138), had a nearly 40% higher all-cause mortality risk in the one month following the disasters, which diminished over the subsequent nine years, but was maintained at 5.6% at nine years. 397 > Nephritis-related death was 27% greater at one year post-Katrina in survivors. 397 > Immune system dysregulation can result, leading to increased secondary viral and other infectious disease susceptibility and poorer oral health.…”
Section: Covid-19 and Toxic Stressmentioning
confidence: 92%